If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5(8-2x)=6(4x-7)*14
We move all terms to the left:
5(8-2x)-(6(4x-7)*14)=0
We add all the numbers together, and all the variables
5(-2x+8)-(6(4x-7)*14)=0
We multiply parentheses
-10x-(6(4x-7)*14)+40=0
We calculate terms in parentheses: -(6(4x-7)*14), so:We get rid of parentheses
6(4x-7)*14
We multiply parentheses
336x-588
Back to the equation:
-(336x-588)
-10x-336x+588+40=0
We add all the numbers together, and all the variables
-346x+628=0
We move all terms containing x to the left, all other terms to the right
-346x=-628
x=-628/-346
x=1+141/173
| 0.4x^2+7.2x=-1 | | 5-x/8=8 | | 0.4x^2+7.2x=1 | | 20g^2-4g-8=0 | | 7y-6=2y | | 2(3x-4)=x | | n-3/4=7 | | 3n-5=5n-20 | | 2(x-8)=x-5 | | 8b=-56 | | 8(3w+6)/3=-6 | | 2(x+19)=x+13 | | 13/x+8=41 | | 2(2x+16)=x+14 | | -4+3×=-12+9x | | 10m+m=100 | | 15t-3=13t-5 | | -7u=17.5 | | -4+3x=-12+9× | | 7x+14=9x-1 | | 13*x=156 | | t÷5-4=13 | | 3x-3=2(x+2 | | z10+7=4 | | 4x=6(x-3 | | 3m+5=14m= | | (x-2)/8=-6 | | 5-x/9=-5 | | 9x+7-4x=3x+x+11 | | 2c+5c=c-8 | | 5x-12=88. | | 19±k=4 |